Hypometabolism and hypothermia in the rat model of endotoxic shock: independence of circulatory hypoxia. (17th July 2014) - Corrigan, Joshua J.; Fonseca, Monique T.; Flatow, Elizabeth A.; Lewis, Kevin; Steiner, Alexandre A.
Abstract : Key points: The hypometabolic, hypothermic response that often replaces fever in endotoxic shock might be consequential to hypoxia, but the available evidence is circumstantial. Here, this hypothesis was tested in an unprecedented experimental preparation that provides simultaneous measurements of oxygen delivery and consumption in rats whose ability to regulate body temperature has not been disrupted by anaesthetics. The results are striking for indicating that hypometabolism and hypothermia in endotoxic shock occur independently of global or tissue hypoxia. The results also demonstrate that a switch in thermal response from fever to hypothermia serves as a pre‐emptive strategy to avoid hypoxia in endotoxic shock. These findings are potentially relevant to critical care, as interventions aimed at elevating oxygen delivery in patients with septic shock are based on the (perhaps erroneous) premise that circulatory hypoxia is the cause of hypometabolism in this patient population. Abstract: We tested the hypothesis that development of hypothermia instead of fever in endotoxic shock is consequential to hypoxia. Endotoxic shock was induced by bacterial lipopolysaccharide (LPS, 500 μg kg −1 i.v. ) in rats at an ambient temperature of 22°C. A β3 ‐adrenergic agonist known to activate metabolic heat production, CL316, 243, was employed to evaluate whether thermogenic capacity could be impaired by the fall in oxygen delivery ( D ̇ O 2 ) during endotoxic shock. This possibility was rejected as CL316, 243 (0.15 mg kg −1 i.v. ) evoked similar rises in oxygen consumption ( V ̇ O 2 ) in the presence and absence of endotoxic shock. Next, to investigate whether a less severe form of circulatory hypoxia could be triggering hypothermia, the circulating volume of LPS‐injected rats was expanded using 6% hetastarch with the intention of improving tissue perfusion and alleviating hypoxia. This intervention attenuated not only the fall in arterial pressure induced by LPS, but also the associated falls in V ̇ O 2 and body temperature. These effects, however, occurred independently of hypoxia, as they were not accompanied by any detectable changes in NAD + /NADH ratios. Further experimentation revealed that even the earliest drops in cardiac output and D ̇ O 2 during endotoxic shock did not precede the reduction in V ̇ O 2 that brings about hypothermia. In fact, D ̇ O 2 and V ̇ O 2 fell in such a synchrony that the D ̇ O 2 / V ̇ O 2 ratio remained unaffected. Only when hypothermia was prevented by exposure to a warm environment (30°C) did an imbalance in the D ̇ O 2 / V ̇ O 2 ratio become evident, and such an imbalance was associated with reductions in the renal and hypothalamic NAD + /NADH ratios. In conclusion, hypometabolism and hypothermia in endotoxic shock are not consequential to hypoxia but serve as a pre‐emptive strategy to avoid hypoxia in this model.